Evaluation of Co-Q10 anti-gingivitis effect on plaque induced gingivitis: A randomized controlled clinical trial - Anirban Chatterjee; Abhishek Kandwal; Nidhi Singh; Amit Singh (Wolters Kluwer Medknow Publications, 2012)
Background: Deficiency of Co-Q10 has been found to be responsible for periodontal destruction; therefore, this study was undertaken to evaluate the anti-gingivitis effect of Co-Q10 on plaque induced gingivitis. Materials and Methods: Thirty subjects with plaque induced gingivitis were enrolled in a split mouth randomized controlled trial. For each subject, scaling was randomly performed for any two quadrants, followed by the topical application of Co-Q10 randomly in a previously scaled and as an unscaled quadrant for a period of 28 days. Four treatment options were planned: option A: scaling only; option B: Co-Q10 along with scaling; option C: Co-Q10. Results: Marked reduction in gingival, bleeding, and plaque scores were recorded at the sites where C0-Q10 was applied. Mean±S.D of aforementioned periodontal parameters at 28th day showed significant reduction for option A, B, and C when compared with baseline. Conclusion: Promising results were obtained after the solitary application of Co-Q10 as well as when it was used as an adjunct to scaling and root planing for treatment of plaque induced gingivitis.